Abdominal aortic aneurysm screening: concepts and controversies - Zucker, Evan J.; Prabhakar, Anand M. (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
Abdominal aortic aneurysms (AAAs) are a leading cause mortality and morbidity but often go undiagnosed until late stages unless imaging is performed. In 2005, the United States Preventive Services Task Force (USPSTF) for the first time recommended one-time ultrasound screening for elderly male smokers and selective screening in other populations. These guidelines were reaffirmed and updated in 2014; a proposal for potential further revisions is now in early planning stages. In this article, we review the past and current USPSTF AAA screening recommendations and techniques for performing optimal screening. Evidence supporting screening and alternative guidelines are also discussed. In addition, emerging concepts and controversies in AAA screening are highlighted, including conflicting data on screening benefits, screening underutilization, inconsistent follow-up recommendations, and the potential for duplicative testing, alternative screening modalities, and clinically significant incidental findings.